Beliefs about medicines among Norwegian outpatients with chronic cardiovascular disease. Issue 2 (28th August 2013) - Viktil, Kirsten K; Frøyland, Hilde; Rogvin, Maria; Moger, Tron Anders
Abstract : Objective: To investigate the beliefs of Norwegian outpatients about medicines, and to explore if some patient-specific factors and drug use are associated with the beliefs. Methods: Patients from an outpatient clinic for chronic cardiovascular diseases were referred by physicians to a pharmacist-led medication outpatient clinic. Here the patients were asked to complete the Beliefs about Medicines Questionnaire. Results: 150 patients were included (mean age 70.0 years (range 31–91), 50 (33.3%) women), using a total of 1061 drugs. 91.2% strongly believed in the necessity of their medicines and 29.7% had strong concerns. Multivariate regression analyses showed that with an increasing number of drugs, the score for necessity was significantly increased (p<0.01). Women were significantly more concerned than men (p=0.03). The older the patient, the higher the score for general harm of medicines (p=0.01). Conclusions: Although the majority of the patients in this study believed in the necessity of their medication, one-third had strong concerns.